EFFECT OF POLLUTION DUE TO COCONUT HUSK RETTING ON THE SPECIES DIVERSITY OF BENTHIC COMMUNITIES OF COCHIN BACKWATERS - Devi, M Ambika; Pillai, N Gopakalakrishna (Indian Journal of Fisheries, 2011)
The variation in abundance, distribution, biomass and species diversity of benthic communities of a retting zone was studied in comparison with that of a non-retting area. The distribution patterns of benthic population was essentially controlled by the hydrographic changes produced as a result of retting. The population density and the species diversity of the benthic faiua were low in the retting zone while a higher species diversity and density were otecrved in the marginal and dean zones. The reduction in the population of the retting ground was the adverse effect of decades of retting activity and the consequent pollution of the region by the retting Icachlcts.